Specification for 13 a plugs, switched and unswitched socket-outlets and boxes (BSI, 1967)
Electric plugs, Electric sockets, Electric connectors, Electric pins, Electric terminals, Portable, Dimensions, Design, Marking, Environment (working), Type testing, Testing conditions, Electrical testing, High-voltage tests, Mechanical testing, Deflection tests, Temperature rise, Thermal testing, Leakage paths, Clearance distances, Earthing, Wear tests, Ageing tests, Environmental testing, Drop tests, Impact testing, Fire tests, Tracking tests, Corrosion tests, Pressure testing, Test equipment, Calibration